Depositional evolution in response to long-term marine transgression in the northern South China Sea - Liu, Entao; Luo, Wei; Yan, Detian; Deng, Yong; Chen, Si; Zhong, Jialin; Jiao, Yangshuo (Frontiers in Marine Science, 2023)
Research on the interaction between depositional evolution process and marine transgression is critical to understanding the transform mechanism of sedimentary systems and guiding hydrocarbon exploration. The early Miocene witnessed the most significant sea-level rise since the Cenomanian, which resulted in extensive marine-influenced deposits worldwide. However, the relationship between the process of depositional evolution and long-term marine transgressions (>1 Ma) remains poorly understood. The Pearl River Mouth Basin in the South China Sea offers a comprehensive deposition record of the early Miocene marine transgression. This study employs high-quality 3D seismic, well-logging, and core data to investigate the impact of the early Miocene transgression on the evolutionary dynamics of the sedimentary system. The regional sea level exhibited a prolonged rise of at least 100 m during the deposition period of the Miocene Zhujiang Formation, corresponding to the long-term marine transgressive in the South China Sea. Throughout this marine transgression, depositional systems developed in the study area include tidal flats, fan deltas, meandering river deltas, and shallow marine shelf sand bodies. The marine transgression process resulted in a significant change in depositional system types, which can be divided into seven units from Unit 1 at the bottom to Unit 7 at the top.The predominant deposition environment transitioned from tidal flats in Units 1-3 to meandering river deltas in Units 4-5, and finally to shallow marine shelf systems in Units 6-7. In the early stage (Units 1-3), the regional uplifts hindered sea level transgression and caused erosion, leading to the development of small-scale proximal fan deltas. In the middle stage (Units 4-5), these regional uplifts submerged, and 3 meandering river deltas dominated with sediments derived from distant extrabasinal sources. During the late stage (Units 6-7), regional sea levels reached their peak, transforming the entire basin into a shallow marine shelf system. Additionally, this marine transgression significantly influenced the distribution of hydrocarbon resources.Notably, the shallow marine shelf sand bodies in Units 6-7 warrant substantial attention for future exploration. This study outlines the complicated transitional processes within depositional systems during long-term marine transgression events, holding relevance for the global evolution of marginal sea basins.